2013
DOI: 10.2106/jbjs.k.01081
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Nonunion in Patients with Intracapsular Femoral Neck Fractures Treated with Three Cannulated Screws Placed in Either a Triangle or an Inverted Triangle Configuration

Abstract: Screw fixation with a triangle configuration, a displaced fracture, and poor reduction are risk factors for nonunion in intracapsular femoral neck fractures treated with fixation with multiple screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(128 citation statements)
references
References 22 publications
3
123
1
1
Order By: Relevance
“…Minimal displacement, adequate stability, sufficient nutrition and absence of infection are some of the factors that support fracture repair. Western literature identify the risk factors for non-union to include displacement, smoking/nicotine use, infection, magnitude of injury, biomechanical instability, malnutrition and vitamin deficiency, iatrogenic factors, diabetes mellitus and nonsteroidal anti-inflammatory drugs use [6,7,[13][14][15]. The role of osteoporosis is inconclusive [13].…”
Section: Discussionmentioning
confidence: 99%
“…Minimal displacement, adequate stability, sufficient nutrition and absence of infection are some of the factors that support fracture repair. Western literature identify the risk factors for non-union to include displacement, smoking/nicotine use, infection, magnitude of injury, biomechanical instability, malnutrition and vitamin deficiency, iatrogenic factors, diabetes mellitus and nonsteroidal anti-inflammatory drugs use [6,7,[13][14][15]. The role of osteoporosis is inconclusive [13].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding fixation with three screws, experimental studies have shown increased mechanical stability using a triangular pattern compared to a vertical screw orientation and that the apex down configuration reduces the risk of a later subtrochanteric fracture compared to apex up configuration (Selvan et al 2004, Oakey et al 2006, Lichtblau et al 2008. A recent clinical report including 202 patients treated for a femoral neck fracture with either a triangle screw configuration or an inverted triangle configuration, found a significant difference in union rate in favor of the inverted triangle configuration (Yang et al 2013). They also discussed an apparent increased risk of subtrochanteric fractures when two distal screws are placed horizontally.…”
Section: Multiple Pins and Screwsmentioning
confidence: 99%
“…Another departure from the traditional inverted triangle configuration is the use of triangular parallel screws, which feature 2 inferior screws and 1 superior screw. Yang et al found that femoral neck fractures stabilised the triangle configuration and had a significantly higher nonunion rate than those fixed with the traditional inverted triangle pattern [17].…”
Section: Biomechanical Studiesmentioning
confidence: 99%